Summary of Glaciological Studies in Mizuho Plateau (Special Issue of the Proceedings of the First Symposium on Antarctic Meteorology and Glaciology) - Tamotsu ISHIDA (National Institute of Polar Research, 1979)
A summary report of the traverse glaciology proiect accomplished by the Japanese Antarctic Research Expedition in 1969-1975 was published in 1978 under the title of "Glaciological Studies in Mizuho Plateau, East Antarctica, 1969- 1975" as a special issue of Memoirs of National Institute of Polar Research, No 7 This paper outlines the abovementioned summary report